If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + -5) + 22 = 0 Reorder the terms: 2(-5 + 6x) + 22 = 0 (-5 * 2 + 6x * 2) + 22 = 0 (-10 + 12x) + 22 = 0 Reorder the terms: -10 + 22 + 12x = 0 Combine like terms: -10 + 22 = 12 12 + 12x = 0 Solving 12 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = 0 + -12 12x = 0 + -12 Combine like terms: 0 + -12 = -12 12x = -12 Divide each side by '12'. x = -1 Simplifying x = -1
| 75x+300=100x+200 | | 2-4y=4y-4 | | x^3-5x^2-8x=0 | | -6(x-3)-20=-2 | | -7h-7h-h=-15 | | 3(x+6)=12-5 | | X^3=x^2+7x | | 12t(t-5)=0 | | 2(8n+3)+10= | | 2q-q=6 | | 21x-28=8x-48+10 | | 17a-12a=20 | | (7(9-z)/6)=-z | | 58m+129=658 | | -0.6x+0.7x-1=1 | | 24-3x=-7(3-6x) | | t^6+6t^3=27 | | -7.7-4y-7.7-2y=-5y-7.5 | | (x-4)*(x+3)=(x-2)*(x-1) | | 3+7(2-5)+4= | | 3x-150=-450 | | 3.5x=4.7 | | -1/10(10)+4= | | -(1-1)+3= | | .25w+2.5=.5w+1.33 | | 2x-52+5x=46 | | (9q^5-9q^4-3)+(2q^5+4q-1)= | | 2x^3-3x^2+12x-18=0 | | 3(2+x)=18 | | y+2=0.6(x-1) | | 5x+10y-12z=0 | | 9x+2-5x=10+3x+1 |